Solitudes in Shared Spaces: Aboriginal and EuroCanadian Anglicans in the Yukon and the Northwest Territories in the Post-Residential School Era - Cheryl, Gaver (Université d'Ottawa / University of Ottawa, 2011)
This thesis examines the current relationship between Aboriginal and EuroCanadian Anglicans in the Northwest Territories and the Yukon as they seek to move beyond past hurts into a more positive future. After three field trips to Canada's North, visiting seven communities and interviewing seventy-nine individuals, complemented by archival research, I realized the dominant narrative based on a colonialism process linking residential schools, Christian Churches and federal government in a concerted effort to deliberately destroy Aboriginal peoples, cultures, and nations was not adequate to explain what happened in the North or the relationship that exists today. Two other narratives finally emerged from my research. The dominant narrative on its own represents a simplistic, one-dimensional caricature of Northern history and relationships. The second narrative reveals a more complex and nuanced history of relationships in Canada's North with missionaries and residential school officials sometimes operating out of their ethnocentric and colonialistic worldview to assimilate Aboriginal peoples to the dominant society and sometimes acting to preserve Aboriginal ways, including Aboriginal languages and cultures, and sometimes protesting and challenging colonialist policies geared to destroying Aboriginal self-sufficiency and seizing Aboriginal lands. The third narrative is more subtle but also reflects the most devastating process. It builds on what has already been acknowledged by so many: loss of culture. Instead of seeing culture as only tangible components and traditional ways of living, however, the third narrative focuses on a more deep-seated understanding of culture as the process informing how one organizes and understands the world in which one lives. Even when physical and sexual abuse did not occur, and even when traditional skills were affirmed, the cultural collisions that occurred in Anglican residential schools in Canada's North shattered children's understanding of reality itself. While the Anglican Church is moving beyond colonialism in many ways - affirming Aboriginal values and empowering Aboriginal people within the Anglican community, it nevertheless has yet to deal with the cultural divide that continues to be found in their congregations and continues to affect their relationship in Northern communities where Aboriginal and EuroCanadian people worship together yet remain separate.